Lymphocytes Contribute to the Pathophysiology of Neonatal Brain Injury - Nazmi, Arshed; Albertsson, Anna-Maj; Rocha-Ferreira, Eridan; Zhang, Xiaoli; Vontell, Regina; Zelco, Aura; Rutherford, Mary; Zhu, Changlian; Nilsson, Gisela; Mallard, Carina; Hagberg, Henrik; Lai, Jacqueline C. Y.; et al. (Frontiers in Neurology, 2018)
Background: Periventricular leukomalacia (PVL) is the most common form of preterm brain injury affecting the cerebral white matter. This type of injury involves a multi-phase process and is induced by many factors, including hypoxia-ischemia (HI) and infection. Previous studies have suggested that lymphocytes play a significant role in the pathogenesis of brain injury, and the aim of this study was to determine the contribution of lymphocyte subsets to preterm brain injury. Methods: Immunohistochemistry on brain sections from neonatal mice was performed to evaluate the extent of brain injury in wild-type and T cell and B cell-deficient neonatal mice (Rag1−/− mice) using a mouse model of HI-induced preterm brain injury. Flow cytometry was performed to determine the presence of different types of immune cells in mouse brains following HI. In addition, immunostaining for CD3 T cells and CD20 B cells was performed on postmortem preterm human infant brains with PVL. Results: Mature lymphocyte-deficient Rag1−/− mice showed protection from white matter loss compared to wild type mice as indicated by myelin basic protein immunostaining of mouse brains. CD3+ T cells and CD20+ B cells were observed in the postmortem preterm infant brains with PVL. Flow cytometry analysis of mouse brains after HI-induced injury showed increased frequency of CD3+ T, T and B cells at 7 days after HI in the ipsilateral (injured) hemisphere compared to the contralateral (control, uninjured) hemisphere. Conclusions: Lymphocytes were found in the injured brain after injury in both mice and human, and lack of mature lymphocyte protected neonatal mice from HI-induced brain white matter injury. This finding provides insight into the pathology of perinatal brain injury and suggests new avenues for the development of therapeutic strategies.